THE INFLUENCE OF INSTITUTIONAL OWNERSHIP AND DIVIDEND POLICY COMPANY SIZE ON DEBT POLICY - Selpi Kurniawati; Destia Aktarina; Iin Hendrayani; Debi Carolina; Muhamad Helmi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2023)
Debt policy is influenced by various factors including company size, liquidity, company profitability, company internal conditions, asset structure, dividend policy, institutional ownership, managerial ownership, and company growth. The purpose of this study is to find out how the partial and simultaneous influence of institutional ownership, dividend policy, company size, and debt policy on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research method is quantitative. The data analysis method in this research is descriptive and verification. This study uses samples from the food and beverage sub-sector companies listed on the Indonesia Stock Exchange which were selected using the purposive sampling method. The population of this study was 30 companies with a sample of 8 companies. The results of this study indicate that there is a partial effect of institutional ownership and company size on debt policy, while the dividend policy partially has no effect on debt policy in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the 2017- 2021 season. The coefficient of determination is the ability of variable X to influence variable Y, while the results of the coefficient of determination produced are 25.2% so it can be interpreted that the influence of institutional ownership (X1) and company size (X3) on debt policy (Y) is 25.2% and the remaining 74.